INVESTIGATION OF THE INFLUENCE OF COMPREHENSIVE HYDROSTATISTICAL PRESSURE ON THE ELECTRICAL PROPERTIES OF N-SI, N-SI AND N-SI SAMPLES (Scientific journal of the Fergana State University, 2023)
The effect of all-round hydrostatic compression (0÷60∙108 Pa) on the electrical properties of silicon single crystals compensated with nickel and gadolinium has been studied. It has been established that the baric dependence of the resistivity of n-Si and n-Si samples, measured in the dynamic mode, is nonmonotonic, and the change in resistivity at low pressures ≥2∙108 Pa is irreversible, which is due to decay of impurity deposits of nickel and gadolinium.